Exploring controls of the early and stepped deglaciation on the western margin of the British Irish Ice Sheet. (2nd June 2021) - Benetti, Sara; Chiverrell, Richard C.; Cofaigh, Colm Ó; Burke, Matt; Medialdea, Alicia; Small, David; Ballantyne, Colin; Bateman, Mark D.; Callard, S. Louise; Wilson, Peter; Fabel, Derek; Clark, Chris D.; et al.
ABSTRACT: New optically stimulated luminescence dating and Bayesian models integrating all legacy and BRITICE‐CHRONO geochronology facilitated exploration of the controls on the deglaciation of two former sectors of the British–Irish Ice Sheet, the Donegal Bay (DBIS) and Malin Sea ice‐streams (MSIS). Shelf‐edge glaciation occurred ~27 ka, before the global Last Glacial Maximum, and shelf‐wide retreat began 26–26.5 ka at a rate of ~18.7–20.7 m a –1 . MSIS grounding zone wedges and DBIS recessional moraines show episodic retreat punctuated by prolonged still‐stands. By ~23–22 ka the outer shelf (~25 000 km 2 ) was free of grounded ice. After this time, MSIS retreat was faster (~20 m a –1 vs. ~2–6 m a –1 of DBIS). Separation of Irish and Scottish ice sources occurred ~20–19.5 ka, leaving an autonomous Donegal ice dome. Inner Malin shelf deglaciation followed the submarine troughs reaching the Hebridean coast ~19 ka. DBIS retreat formed the extensive complex of moraines in outer Donegal Bay at 20.5–19 ka. DBIS retreated on land by ~17–16 ka. Isolated ice caps in Scotland and Ireland persisted until ~14.5 ka. Early retreat of this marine‐terminating margin is best explained by local ice loading increasing water depths and promoting calving ice losses rather than by changes in global temperatures. Topographical controls governed the differences between the ice‐stream retreat from mid‐shelf to the coast.